Les assurances du chantier – biens et responsabilités - Barry, Claude (Assurances, 1989)
The author discusses the nature and scope of Builder's Risk Insurance and then looks at coverage for damages caused to work under construction, public liability arising from damages to a third party and damages caused by professionals.